SOCIAL REPRESENTATIONS ABOUT AGING (Fiep Bulletin - online, 2012)
This study has the objective of understand the social representations of aging. This is an exploratory study with 240 elderly an interview answered composed by Test Free Word Association using the inductive stimulus "aging." From the data collected we carried out a semantic analysis with the help of the software Alceste who indicated five classes or themes: images of old, aging as gains and losses, social and family support, socio-emotional and practical effects of aging. The elderly represent aging as a stage that has many health problems, such as osteoporosis, high blood pressure, rheumatism and back problems, as positive and negative dimensions is associated with aging: experience, appreciation, respect, peace, peace, and retirement.
Keywords: Health; Aging; Social Representations